Evaluation of the anti-inflammatory properties of secoisolariciresinoldiglucoside in a rodent model of joint inflammation - SADIQ S. MAREAI; KAVISHANKAR GAWLI; RAJESHA J (International Journal of Pharma and Bio Sciences, 2016)
The anti-inflammatory potential of secoisolariciresinol diglucoside (SDG) in modulating the immune system response to an inflammatory substance was evaluated. The animals were orally treated with 20, 40 and 80 mg/kg.b.w of SDG to carrageenan-induced rats. The thickness of the rat paw was measured using Plethysmometer at 0-24 h. The tissue extracts and sera of animals were used for the analysis of nitric oxide, Prostaglandin E2 (PGE2) and Nerve Growth Factor (NGF) using specific kits. SDG at 80 mg/kg.b.w. for one-day period before the carrageenan injections significantly reduced (P < 0.05) paw swelling (45.18 %). Furthermore, there was a decrease in nitrite levels in paw tissue and serum by 72.4 and 53.6% respectively. The level of PGE2 was diminished by 39.21 and 32.56% and NGF levels by 43.1 and 46.1% respectively, when compared with the control. SDG could be useful to improve localized and systemic inflammatory responses against a variety of inflammatory disorders.